Analysis and design of photovoltaic three-phase grid-connected inverter using passivity-based control - Zainab Mahmood Abed; Turki Kahawish Hassan; Kassim Rasheed Hameed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper presents photovoltaic three-phase grid-connected inverter with an inductor-capacitor-inductor (LCL)-filter. For robustness against variation of filter parameters and external disturbance, the passivity-based control (PBC) method has been adopted. In this method, there are two interactively coupled feedforward terms and three damping gains in the control loops which are designed to limit the steady state error of grid current. Boost converter with P&O maximum power point tracker (MPPT) is used for each photovoltaic (PV) string to extract maximum power and to raise the PV voltage to a value suitable for the grid-connected inverter. The outputs of all boost converters are connected in parallel and controlled to fixed reference voltage using proportional-integral (PI) controller to make the direct-current (DC) link voltage robust against variations in sun radiation intensity and system parameters change. The suggested system is analyzed, designed and simulated using PSIM program. 1 kW, 2kW, and 3kW PV systems connected to grid of 220V/50Hz are tested and the results show the validity of the suggested grid-connected PV systems and robustness against filter parameters variation.